(untitled) (The International Journal for Scientific Research, 2024)
The study aimed to identify the impact of digital transformation in its dimensions on achieving institutional excellence. The researcher used the descriptive analytical approach. To obtain data from the study population, which numbered (70) employees, a questionnaire form was used, and after modifying and judging it, it was randomly distributed to a random sample consisting of (59) employees After examining it, a number of (16) questionnaires were excluded because they did not complete the data, and therefore the number of questionnaires that were subjected to statistical analysis was (43). The study reached several results, the most important of which are: The level of digital transformation increased in its four dimensions, where the human resources dimension came in first place, followed by the organizational structure dimension, then the strategic planning dimension, and in last place was the infrastructure dimension. The results also showed an impact of the dimensions of digital transformation (organizational structure, infrastructure, connectivity). Except for the human resources dimension, where the results showed that it had no effect on the institutional excellence of the Libyan Guarantee Insurance Company.